Do Teachers Use Textbooks as Their Curriculum? - Lindemann, Krista; Schroeder, Mikayla (My University, 2011)
Many teachers do not have helpful language standards, or a workable curriculum, thus frequently textbooks become the backbone of the course. This practice clearly does not benefit language learners, because textbooks are not focused specifically on all of the unique learners' goals, needs, or learning styles that exist in all ESL/EFL classrooms, nor do they focus on the various characteristics within a context. This qualitative and quantitative research study investigated how four populations of language teachers interacted with their textbook, curriculum and materials in relation to the quality of their teacher training experiences.
Color poster with text and chart.
Keywords: English language--Textbooks for foreign speakers; Curriculum planning; Posters; Teachers--Training of--Research